HUBUNGAN PENGALAMAN PERAWAT DAN KEBERHASILAN RESUSITASI JANTUNG PARU DI RUANG IGD,ICU DAN ICCU RSUD PROF.W.Z JOHANNES KUPANG - Aty, Yoani Maria Vianney Bita; Blasius, Gadur (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Cardiovascular disease is a global threat and is the number one cause of death worldwide. Until now, CPR is a very vital management in cases of cardiac arrest. The results of the initial survey found that nurses often found patients who had cardiac arrest, which required CPR. Some patients were saved and some died. Based on this, it is necessary to conduct research on the experience of ER, ICU and ICCU nurses in performing cardiopulmonary resuscitation. The aim of the study was to determine the relationship between nurses' experience and the success of cardiopulmonary resuscitation in the ER, ICU and ICCU RSUD Prof. Dr. W. Z. Johannes Kupang. This research is a quantitative research, correlation study design. The sample used is 41 nurses. Quota sampling technique. Analysis using Chi Square. The results showed that most of the respondents had sufficient experience of cardiopulmonary resuscitation, namely 37 people (90.8%). Most of the respondents managed to perform CPR, namely 34 people (82.9%). There is a relationship between experience and the success of cardiopulmonary resuscitation with a p value of 0.0001. Suggestions Training for emergency cardiac arrest needs to be carried out routinely to improve the quality of CPR